PARIS: protocol for a prospective single arm, theory-based, group-based feasibility intervention study to increase Physical Activity and reduce sedentary behaviouR after barIatric Surgery. Issue 12 (22nd December 2021) - James, Jennifer; Hardeman, Wendy; Eborall, Helen; Goodall, Mark; Wilding, John
Abstract : Introduction: Increased physical activity and reduced sedentary behaviour can encourage favourable outcomes after bariatric surgery. However, there is a lack of evidence as to how to support patients with behaviour change. The aim of this study is to assess the feasibility of a physiotherapist led, online group-based behaviour change intervention to increase physical activity and reduce sedentary behaviour following bariatric surgery. Methods and analysis: Single arm feasibility study of a theory and evidence-based group behaviour change intervention based on the Behaviour Change Wheel and Theoretical Domains Framework using behaviour change techniques from the Behaviour Change Technique Taxonomy v1. The intervention has eight objectives and specifies behaviour change techniques that will be used to address each of these. Groups of up to eight participants who have had surgery within the previous 5 years will meet weekly over 6 weeks for up to 1½ hours. Groups will be held online led by a physiotherapist and supported by an intervention handbook. Feasibility study outcomes include: rate of recruitment, retention, intervention fidelity, participant engagement and acceptability. Secondary outcomes include: physical activity, sedentary behaviour, body composition, self-reported health status and will be analysed descriptively. Change in these outcomes will be used to calculate the sample size for a future evaluation study. Qualitative interviews will explore participants' views of the intervention including its acceptability. Data will be analysed according to the constant comparative approach of grounded theory. Ethics and dissemination: This study has National Health Service Research Ethics Committee approval; Haydock 20/NW/0472. All participants will provide informed consent and can withdraw at any point. Findings will be disseminated through peer-reviewed journals, conference and clinical service presentations. Trial registration number: ISRCTN31524689 .